Handbook of Ecomaterials 2017
DOI: 10.1007/978-3-319-48281-1_72-1
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Nanoparticle Additives for Lubricants and Their Tribological Characterization

Abstract: Worldwide manufacturing, as well as the transportation industry, is greatly affected by the rising costs of energy, maintenance, replacement of expensive and crucial components, and environmental legislations. Diverse solutions have been proposed to meet these challenges: more efficient processes that minimize energy consumption, weight reductions, as well as achieving longer maintenance periods and longer replacement times for tooling and components. In order to find a solution for these issues, nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…The toroidal-like structures are closely related to the well-known sphere-like nanostructures. As mentioned by Kharissova et al [ 37 ], these torus-like materials have been studied more theoretically than experimentally. However, scientific studies have shown their superb properties and promising applications.…”
Section: Introductionmentioning
confidence: 99%
“…The toroidal-like structures are closely related to the well-known sphere-like nanostructures. As mentioned by Kharissova et al [ 37 ], these torus-like materials have been studied more theoretically than experimentally. However, scientific studies have shown their superb properties and promising applications.…”
Section: Introductionmentioning
confidence: 99%